2022
DOI: 10.1093/femsle/fnac103
|View full text |Cite
|
Sign up to set email alerts
|

Akkermansia muciniphila attenuates LPS-induced acute kidney injury by inhibiting TLR4/NF-κB pathway

Abstract: Acute kidney injury (AKI) is a global public health hazard with high morbidity and mortality. Sepsis accounts for nearly half of all causes of AKI. Scientists have made a great effort to explore effective therapeutic agents with limited side effects in the treatment of AKI, but have had little success. With the development of gut flora study, Akkermansia muciniphila (A. muciniphila) has been proven to prevent different organs by regulating the inflammatory response. However, the reno-protective function is sti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Of note, the statistically significant difference in Verrucomicrobia was also observed at the species level, for Akkermansia muciniphila (A. muciniphila; p value = 0.005). A recent report observed that pretreatment with A.muciniphila protected against lipopolysaccharide-induced acute kidney in mice (22), implying that this strain is physiologically important.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Of note, the statistically significant difference in Verrucomicrobia was also observed at the species level, for Akkermansia muciniphila (A. muciniphila; p value = 0.005). A recent report observed that pretreatment with A.muciniphila protected against lipopolysaccharide-induced acute kidney in mice (22), implying that this strain is physiologically important.…”
Section: Discussionmentioning
confidence: 94%
“…A recent report observed that pre-treatment with A . muciniphila protected against lipopolysaccharide-induced acute kidney in mice (22), implying that this strain is physiologically important.…”
Section: Discussionmentioning
confidence: 99%
“…Since the kidneys are the primary excretory organs for metabolites and toxins, the renal tubular epithelium is susceptible to various damages. LPS is a significant contributor to AKI. Furthermore, renal tubular epithelial cells are more easily exposed to a high concentration of the LPS microenvironment from the intestinal entrance, which significantly impacts the morphology and function of the renal tubular epithelial cells. , After 24 h and 48h incubation, cell viability cocultured with LPS (10 μg/mL) was reduced to 87.5 ± 5.7 and 79.8 ± 1.4% compared to the control group ( p < 0.05). The 20 μM PJ16 noticeably prevented LPS-induced cell injury with the cell survival rate of 100 ± 1.5 and 95.9 ± 5.5% ( p < 0.05) (Figure A).…”
Section: Resultsmentioning
confidence: 99%
“…Studies have shown that “metabolic endotoxemia” encourages the onset of obesity and metabolic disorders, which is also the primary cause of AKI . Through the TLR4 signaling pathway, lipopolysaccharide (LPS) contributes to the onset and progression of kidney disease. Therefore, in vitro models of LPS-stimulating macrophages and renal tubular epithelial cells were constructed to detect how PJ16 modulates macrophage function and protects LPS-injured renal tubular epithelial cells. Consistent with the results in vitro, we established a unilateral ureteral obstruction (UUO) mouse model to verify the effect of PJ16 in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…Akkermansia protects the intestinal mucus layer and maintains intestinal homeostasis, reducing the entry of LPS into the bloodstream ( 89 ). Vesicles secreted by Akkermansia are also able to reduce the expression of TLR4, thereby regulating the NF-κB pathway ( 90 ). Therefore, insufficient Akkermansia genera might disrupt the balance of Th17/Treg through activating TLR4 signaling pathway.…”
Section: Discussionmentioning
confidence: 99%